Comparing expeditious procedures for the seismic vulnerability assessment on the European territorial context: reliability, feasibility, cost, and time consumption. Issue 7 (17th November 2018) - Taffarel, Sabrina; da Porto, Francesca; Valluzzi, Maria Rosa; Modena, Claudio
ABSTRACT: The definition of strategies for the preservation and protection of cultural heritage is a topical issue, especially in view of the increasing relevance of the theme of seismic risk mitigation and reduction. The prediction of the impact an earthquake could have on existing buildings requires the knowledge of their dynamic behaviour. The procedure to be adopted for this purpose is quite complex and onerous in terms of costs, time, and implementation, especially when the study concerns territorial areas rather than single buildings. The definition of methodologies aimed at respecting the principles of economic sustainability and preserving human life and architectural heritage is of paramount importance to assess seismic vulnerability using available resources. Rapid methods for the seismic vulnerability assessment, aimed at defining buildings vulnerability and intervention priority lists, must be implemented to guarantee the preservation of historical centers. This article describes the application to some case studies of different methods aimed at creating fragility curves for the vulnerability assessment on the European territorial context. The comparison between a deterministic approach and a new probabilistic one is performed for all case studies, to define the most suitable methodology in terms of reliability and savings in cost and time.